1991
DOI: 10.1021/ja00016a094
|View full text |Cite
|
Sign up to set email alerts
|

A new chiral ligand for the asymmetric conjugate addition of organocopper reagents to enones

Abstract: cussions. The financial help of Rh6ne-Poulenc Company through a grant to S.M. is also greatly appreciated. 1r(13) Typical procedure: To a suspension of CUI (476 mg; 2.5 mmol) in T H F (40 mL) is added ligand 1 (3.4 mL of a 1.5 N solution in toluene; 5.1 mmol) at -30 OC. The temperature is allowed to rise, and solubilization is usually observed around IO OC. After stirring for 15 min, the solution is cooled to -40 OC and nBuLi (1.45 mL of a 1.6 M solution in hexane; 2.3 mmol) is added. The solution, which turns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(21 citation statements)
references
References 1 publication
(1 reference statement)
0
20
0
1
Order By: Relevance
“…5,6 Although other ligand types have been disclosed, the ones based on phosphorus are the most effective. Most ligands are monodentate, but some are bidentate, either P,P or P,N.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Although other ligand types have been disclosed, the ones based on phosphorus are the most effective. Most ligands are monodentate, but some are bidentate, either P,P or P,N.…”
Section: Methodsmentioning
confidence: 99%
“…4 Later on, Alexakis introduced, in 1991, the use of chiral trivalent phosphorus ligands and demonstrated their efficiency. 5 For catalytic amount of copper salt, and therefore chiral ligand, the same authors showed that dialkylzinc reagents were more appropriate than the classical use of Grignard reagents. 6 It followed that in the last 6-7 years, a tremendous effort has been put, by more and more authors, in disclosing more and more efficient chiral ligands (>350 !…”
Section: The Conjugate Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 1993, all authors have relied upon the use of Grignard reagents, whereupon we introduced the idea of using diorganozinc reagents instead [4]. The needed chiral information was brought by a trivalent phosphorus ligand, a type of chiral ligand we also introduced in organocopper chemistry, in 1991 [5]. This combination of reagents has, since then, found a widespread use (Scheme 3).…”
Section: Conjugate Additionmentioning
confidence: 99%
“…[8] Further brilliant successes have also been continuously reported by using dialkylzinc reagents as sources of alkyl nucleophiles, which are characterized by the use of a phosphorus-based ligand for copper. [9,10] Since the development of a phosphoroamidite by Alexakis group, [11,12] binaphthol-based phosphorus ligands have been demonstrated to be really effective giving over 90 % ee by the endeavors of the Feringa [13] and Zhang [14] groups. Highly efficient phosphane ligands were also developed by Imamoto [15] and Hoveyda.…”
Section: Introductionmentioning
confidence: 99%